A Developmental and Sequenced One-to-One Educational Intervention for Autism Spectrum Disorder: A Randomized Single-Blind Controlled Trial - Tanet, Antoine; Hubert-Barthelemy, Annik; Crespin, Graciela C.; Bodeau, Nicolas; Cohen, David; Saint-Georges, Catherine; , The GPIS Study Group; Bur, Véronique; Brellier, Aude; Clément, Marie-Noëlle; Chartier, Christophe; Ducateau, Claire; et al. (Frontiers in Pediatrics, 2016)
Introduction Individuals with autism spectrum disorder (ASD) who also exhibit severe-to-moderate ranges of intellectual disability (ID) still face many challenges (i.e., less evidence-based trials, less inclusion in school with peers). Methods We implemented a novel model called the “Developmental and Sequenced One-to-One Educational Intervention” (DS1-EI) in 5- to 9-year-old children with co-occurring ASD and ID. The treatment protocol was adapted for school implementation by designing it using an educational agenda. The intervention was based on intensity, regular assessments, updating objectives, encouraging spontaneous communication, promoting skills through play with peers, supporting positive behaviors, providing supervision, capitalizing on teachers’ unique skills, and providing developmental and sequenced learning. Developmental learning implies that the focus of training is what is close to the developmental expectations given a child’s development in a specific domain. Sequenced learning means that the teacher changes the learning activities every 10–15 min to maintain the child’s attention in the context of an anticipated time agenda. We selected 11 French institutions in which we implemented the model in small classrooms. Each institution recruited participants per dyads matched by age, sex, and developmental quotient. Patients from each dyad were then randomized to a DS1-EI group or a Treatment as usual (TAU) group for 36 months. The primary variables – the Childhood Autism Rating scale (CARS) and the psychoeducational profile (PEP-3) – will be blindly assessed by independent raters at the 18-month and 36-month follow-up. Discussion and baseline description We enrolled 75 participants: 38 were randomized to the DS1-EI and 37 to the TAU groups. At enrollment, we found no significant differences in participants’ characteristics between groups. As expected, exposure to school was the only significant difference [9.4 (±4.1) h/week in the DS1-EI group vs. 3.4 (±4.5) h/week in the TAU group, Student’s t-test, t = 5.83, p < 0.001]. Ethics and dissemination The protocol was authorized by the competent national regulatory authority (Agence nationale de sécurité du médicament et des produits de santé) and approved by the local Ethics Committee (Comité de Protection des Personnes) at the University Hospital Saint-Antoine (May 7, 2013). The findings will be disseminated through peer-reviewed journals and national and international conferences. Trial registration numbers ANSM130282B-31 (April 16 2013) and ACTRN12616000592448 (May 6 2016).